Dukungan Sosial pada Penderita Kanker - Muhana Sofiati Utami; Nida UI Hasanat (Faculty of Psychology, Universitas Gadjah Mada, 1998)
In Indonesia, death from cancer increase rapidly from year to year. So it is importent to give attention and serious intervention on the problem of cancer. This Study was designed to asses the relationship between social support and depression; to identity the social-support source which contributes the most to cancer patient; an to assessed the level of depression of the cancer patients. The subjects were 51 cancer patients of the radio therapy unit of the RSUP Dr. Sardjito Yogyakarta. The results show that there is a negative correlation between social support and depression. The result also suggests that 46.15% of the subjects are depressed, although they receive high social support (the highest support comes from spouses parents, and families).